Foveal-Sparing Scotomas in Advanced Dry Age-Related Macular Degeneration - Sunness, Janet S. (2008)
Foveal-sparing scotomas are common in advanced dry macular degeneration (geographic atrophy). Foveal preservation may be present for a number of years. Despite good visual acuity, these patients have reduced reading rates. Magnification may not be effective if the text becomes too large to “fit” within the central spared area.